1996
DOI: 10.3109/08916939608995359
|View full text |Cite
|
Sign up to set email alerts
|

The Timing of Immunization Affects the Development of Diabetes in Rodents

Abstract: Animal studies have demonstrated the timing and content of human vaccines can affect the development of diabetes. Clinical trials of new human vaccines are not designed and generally not powered to detect an effect of immunization on the development of IDDM. These animal toxicology studies indicate that the effect of vaccines on human insulin dependent diabetes needs to be examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1
6

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 17 publications
0
25
1
6
Order By: Relevance
“…One potential mechanism of immunization which may actually lower the risk of IDDM is to give the vaccine starting in the first month of life. This method has been associated with a decreased risk of IDDM in both humans [3,35] and animals [36].…”
Section: Resultsmentioning
confidence: 99%
“…One potential mechanism of immunization which may actually lower the risk of IDDM is to give the vaccine starting in the first month of life. This method has been associated with a decreased risk of IDDM in both humans [3,35] and animals [36].…”
Section: Resultsmentioning
confidence: 99%
“…Classen 8,9 has suggested that certain vaccines, if given at birth, may decrease the occurrence of diabetes, whereas if initial vaccination is administered after 2 months of age, the occurrence of diabetes increases. The theory is based on results from experiments in laboratory animals, as well as comparisons of the rates of diabetes between countries with different immunization schedules.…”
Section: Discussionmentioning
confidence: 99%
“…Classen and Classen 8,9 have hypothesized that certain vaccines (eg, hepatitis B, BCG), if given at birth, can decrease the risk of developing type 1 diabetes mellitus, whereas first vaccination at 2 months of life or later can increase the risk of type 1 diabetes. The few studies reported to date, however, have evaluated vaccine exposure without regard to timing.…”
mentioning
confidence: 99%
“…Supposedly, any vaccination after 2 months age increases the risk of type 1 diabetes but if practiced in the first month of life, it protects against type 1 diabetes [53,54].…”
Section: Influenza Vaccine and Diabetesmentioning
confidence: 99%